Influencia del Tinkering en el desarrollo de conceptos de artes plásticas (2017)
"In this work is an investigation that makes use of Tinkering as a method of learning, where it is explored through phenomenography the influence in the development of the concept of plastic arts".-- Tomado del Formato de Documento de Grado.